Case Analysis Of Royal Dutch/Shell Group Of Companies - Mahmoud, Samir A. (2005)
The existence of Royal Dutch in over 140 countries all-around the world has given it more dominance. In this paper, the main focus will be on the Company's main business portfolio, i.e Exploration and production, gas and power and oil products.